ANALISIS TINGKAT KEBERHASILAN DAN STRATEGI PENGEMBANGAN AGROWISATA GUNUNG PRAU MELALUI JALUR PENDAKIAN DESA PATAK BANTENG DI KECAMATAN KEJAJAR KABUPATEN WONOSOBO - Enggal Styawan; Nanik Dara Senjawati; Siti Hamidah (Jurnal Dinamika Sosial Ekonomi, 2017)
This study aims to at analysing the success rates and developing strategy toward the Prau Mount Agrotourism development through hiking route via Patak Banteng Village Kejajar Distric Wonosobo Regency. This study employed descriptive approach. The result of the study is aimed at confirming an approximate relatively-high success rates of Mount Prau agrotourism via Patak Banteng Village. The method of determining the research object of this study is the pusposive method which employed the respondents such as the developer of the tourism, owners of the culinary, owners of the souvenir outlets, and hiking stuffs rent's owners. Methods of gaining the developer respondents is in amount of 30 respondents, while the respondents from owners of the culinary, souvenir outlets, and g stuffs using kuota sampling technique which is in amount of 30 respondents. The technique of collecting data in this study were observation, questionaire, and documentation for finding the primary and secondary data. Then the analysis technique that were emploved in this study were one sample t test, External Factor Evaluation (EFE), Internal Factor Evaluation Matrix (EFI), Internal-External Matrix (1-E), and SWOT matrix. The success rates of Mount Prau agrotourism development via Patak Banteng Village are in high rates while the development strategy after the research was resulted SO strategy Keywords: Success rates, Developing Strategy, Agrotourism, Mount Prau